Education and the Spirit of Man (RLE Edu K) - Pollard, Francis (Routledge Library Editions: Education, 1932)
This volume was the Swarthmore Lecture for 1932, one of an annual series of lectures delivered by and for members of the Society of Friends (Quakers). The lecture discusses the place of education and moral philosophy in the world of the early twentieth century, as well as the place of religious discipline in education. 1. The Seed and the Light. 2. Training and Instruction. 3. Education and Life. 4. Freedom and the Moral Aim. 5. Quakerism and the Mission of Education. 6. Conclusion.